Risk factors associated with the severity of coronary artery disease among patients undergoing coronary angiography and percutanoues coronary intervention in Elkasr Elaini University Hospital : Registry study - Leena Ateeq Mohammed Alyemeni; Amr Alfaramawi; Magdi Mukhtar; Zeinab Ashour (Cairo : Leena Ateeq Mohammed Alyemeni, 2010)
The incidence of coronary artery disease (CAD) has increased in Egypt. We conducted this study to determine the data of CAD patients at our hospital, and to identify the prevalence of conventional risk factors of CAD and their effects on the severity of underlying coronary lesions. To know the demographic, clinical, and angiographic features of patients who underwent coronary angiography or percutanoues coronary interventions at our hospitals
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Cardiology
Issued also as CD
Keywords: CAD risk factors; Coronary angiography; Percutanoues